FREEDOM OF SPEECH IN THE UZBEK LANGUAGE AND THE PROBLEM OF INTERFERENCE IN TEACHING THE SOV MODEL IN JAPANESE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
This article examines the difficulties that arise in teaching Japanese syntax to Uzbek-speaking learners. The relative freedom of word order in the Uzbek language and the fact that meaning is mainly expressed through case markers contrast with the more structurally fixed syntactic model of Japanese. This difference often leads to linguistic interference in the learning process. In particular, errors related to the theme–rheme structure, the use of the particles wa (は) and ga (が), and the positioning of sentence elements are analyzed through specific examples. The study employs a comparative analytical method to examine the syntactic features of Uzbek and Japanese. Based on the findings, methodological recommendations are proposed to improve the effectiveness of teaching Japanese in the Uzbek educational context.